Training and Development's Impact on Staff Contentment and Turnover in Indian Public Banking Sectors - Kumar Singh, Abhishek; Agarwal, Shalu (Journal of Neonatal Surgery, 2025)
This research examines the relationship between training and development initiatives and their impact on employee satisfaction and retention within India's public banking sector. Through comprehensive analysis of data from major public sector banks (PSBs) including State Bank of India, Punjab National Bank, and Bank of Baroda, this study reveals significant correlations between structured training programs and reduced employee turnover rates. The findings indicate that banks with robust training frameworks experience 23% lower attrition rates and 18% higher employee satisfaction scores compared to institutions with minimal development programs. The research methodology employed mixed-methods approach combining quantitative analysis of HR metrics from 15 public sector banks over a five-year period (2019-2023) with qualitative insights from 450 banking professionals across different hierarchical levels